Comparison of Canal Transportation and Centering Ability of One-G, EdgeGlidePath, and Neolix: A MicroComputed Tomography Study of Curved Root Canals - Shiva Shojaeian; Niloofar Mortezapour; Fatemeh Soltaninejad; Nazanin Zargar; Babak Zandi; Yazdan Shantiaee; Amin Bidaki (International Journal of Dentistry)
Aims. A glide path is created prior to root canal instrumentation by nickel-titanium (NiTi) rotary files to increase the efficiency and safety of cleaning and shaping. This study aimed to assess root canal transportation in use of different glide path files in curved canals. Materials and Methods. 30 sound mesiobuccal root canals of mandibular molars with 20° to 40° curvature were selected and randomly assigned to 3 groups of EdgeGlidePath (EGP, EdgeEndo), One-G (Micro-Mega), and Neolix (Neoniti). The specimens were scanned before and after glide path creation by microcomputed tomography (micro-CT). The pre- and postoperative micro-CT scans were superimposed, and the degree of canal transportation and centering ratio were measured at 1, 3, 5, and 7 mm distances from the apical foramen. Statistical Analysis. The data were analyzed by two-way and one-way ANOVA. Results. The effects of distance from the apical foramen and instrument type and the interaction effect of the two were not significant on the centering ability of the files or canal transportation. Conclusion. EdgeGlidePath, One-G, and Neolix files fabricated from the conventional NiTi alloy or heat-treated M-Wire alloy showed similar performance regarding centering ability and canal transportation in glide path preparation in curved canals.